2022
DOI: 10.1177/15910199221140276
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous thrombolysis plus mechanical thrombectomy versus mechanical thrombectomy alone for acute ischemic stroke: A systematic review and updated meta-analysis of clinical trials

Abstract: Background Mechanical thrombectomy (MT) is the gold standard treatment for large vessel occlusion (LVO). A vital factor that might influence MT outcomes is the use of intravenous thrombolysis (IVT). A few clinical trials in this domain thus far have not yielded consistent outcomes. We conducted this meta-analysis to synthesize collective evidence in this regard. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement guidelines were followed, and we performed a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Active research is ongoing in patients with MeVO, 55,[112][113][114][115][116][117][118][119] and new EVT techniques are evolving. [120][121][122][123][124][125][126]…”
Section: Gaps In Knowledgementioning
confidence: 99%
“…Active research is ongoing in patients with MeVO, 55,[112][113][114][115][116][117][118][119] and new EVT techniques are evolving. [120][121][122][123][124][125][126]…”
Section: Gaps In Knowledgementioning
confidence: 99%
“…Recent meta-analyses and randomized clinical trials (RCTs) found no superiority or non-inferiority in functional outcome and mortality at 90 days between patients with a large vessel occlusion (LVO) treated with and without IVT prior to EVT. (2)(3)(4)(5)(6)(7)(8) These studies mainly concerned patients with anterior circulation occlusions.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent meta-analyses and randomized clinical trials found no superiority or noninferiority in functional outcome and mortality at 90 days between patients with an LVO treated with and without IVT before EVT. [2][3][4][5][6][7][8] These studies mainly concerned patients with anterior circulation occlusions.…”
mentioning
confidence: 99%